Do galaxies die? Different views from simulations and observations in the local Universe. Issue 4 (10th August 2021) - Corcho-Caballero, Pablo; Ascasibar, Yago; Scannapieco, Cecilia
ABSTRACT: For years, the extragalactic community has divided galaxies in two distinct populations. One of them, featuring blue colours, is actively forming stars, while the other is made up of 'red-and-dead' objects with negligible star formation. Yet, are these galaxies really dead? Here, we would like to highlight that, as previously reported by several independent groups, state-of-the-art cosmological numerical simulations (EAGLE, IllustrisTNG, MAGNETICUM, and SIMBA) predict the existence of a large number of quenched galaxies that have not formed any star over the last few Gyr. In contrast, observational measurements of large galaxy samples in the nearby Universe (GAMA, SDSS) suggest that even the most passive systems still form stars at some residual level close to sSFR ∼ 10 −12 yr −1 . Unfortunately, extremely low star formation poses a challenge for both approaches. We conclude that, at present, the fraction of truly dead galaxies is still an important open question that must be addressed in order to understand galaxy formation and evolution.